Draft Genome Sequences of Three Human Pathogenic Acinetobacter baumannii Strains - Madhi, Masoumeh (Microbiol Resour Announc, 2019)
Acinetobacter baumannii is an opportunistic human pathogen with the ability to develop multiple resistances against the main antibiotic classes. It causes nosocomial infections, especially in intensive care units. Here, we present the draft genome sequences of three isolates (AB1, AB2, and AB3) from humans, collected from two hospitals in Tabriz, Iran.